Student Motivation in Learning Sports Faal Science Courses - Tedi Purbangkara; Asep Pratama (Universitas Muhammadiyah Enrekang, 2022)
This research is motivated by the many shortcomings that appear, such as students are reluctant to take part in this sport physiology course for various reasons and factors so that both in terms of achieving educational goals, increasing student fitness and developing student movement skills it becomes difficult to fulfill and the learning methods applied. by the lecturer at the location where the activity took place which made students lazy to take part in learning sports physiology courses again, so that students were very enthusiastic and afraid (worried) every time the learning of sports physiology courses took place. This study aims to determine the level of motivation of students at Singaperbangsa Karawang University, Health and Recreational Physical Education Study Program. The design of this research is descriptive research. The method used in this research is a survey method. The population in this study were Semester 3 students at Singaperbangsa University Karawang, Health and Recreational Physical Education Study Program. The subjects used in this study were 100 Semester 3 students. The data collection technique was a questionnaire (questionnaire). The results showed that the level of motivation of Semester 3 students at Singaperbangsa Karawang University Physical Education and Recreation Study Program towards learning sports physiology subjects was in the LESS category with a percentage of 55.45%. Intrinsic motivation with sub-indicators which include Belief, Desire, and Self-confidence has a percentage of 54.84% in the LESS category. For extrinsic motivation with sub indicators which include Environment, Family, and Association has a percentage of 55.98% in LESS.